2016
DOI: 10.1016/s2214-109x(16)00046-2
|View full text |Cite
|
Sign up to set email alerts
|

The UN Commission on Life Saving Commodities 3 years on: global progress update and results of a multicountry assessment

Abstract: Governments of Norway (NORAD) and the UK (DFID).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 1 publication
2
56
0
Order By: Relevance
“…Although the country has healthcare facility infrastructure at the community level, training and refresher trainings are lacking for HSPs in primary healthcare settings on understanding signs and symptoms of disease, treatment dosing, and follow-up. These findings are similar to results of a multi-country assessment [15]. We found that because of insufficient training, HSPs were not able to state the correct dose of amoxicillin for the case management of childhood pneumonia in Digholia, Khulna.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although the country has healthcare facility infrastructure at the community level, training and refresher trainings are lacking for HSPs in primary healthcare settings on understanding signs and symptoms of disease, treatment dosing, and follow-up. These findings are similar to results of a multi-country assessment [15]. We found that because of insufficient training, HSPs were not able to state the correct dose of amoxicillin for the case management of childhood pneumonia in Digholia, Khulna.…”
Section: Discussionsupporting
confidence: 85%
“…Through the UN Commission on Life Saving Commodities, significant progress has been made in the dissemination of WHO treatment policies globally and in policy change for childhood pneumonia and PSBI at the national level in target high-burden countries [15]. The accomplishments in these countries include updating lists of essential medicines to include amoxicillin DT, registering products, coordinating procurement and supply-chain logistics, revising clinical treatment guidelines, developing and delivering training for health workers, developing appropriate job-aids and support materials, and monitoring and evaluating policy implementation and impact [15]. However, these changes in policies and practices must be accepted and implemented at the primary healthcare level to achieve impact.…”
Section: Introductionmentioning
confidence: 99%
“…We differentiated between items that relate directly to a P4P target and those which do not, to examine eventual spillover effects. Items were also classified according to their beneficiary/recipient group along the RMNCH continuum of care based on the WHO classification of priority medicines . For each of these groupings, we generated composite scores based on an unweighted mean score across items in the group, which can be interpreted as the mean percentage availability/stock‐out rate within the grouping across facilities.…”
Section: Methodsmentioning
confidence: 99%
“…According to the United Nations Commission on Life‐Saving Commodities, payment for performance (P4P) is a strategy to improve access to life‐saving commodities for maternal and child health . P4P provides financial incentives to providers and/or healthcare managers based on the achievement of pre‐defined performance targets and is currently being rolled out in many low‐income countries .…”
Section: Introductionmentioning
confidence: 99%
“…Too often, most of the rural health facilities hardly have all these elements needed for delivery of quality healthcare services. In fact, in Uganda like many other LMIC, health facilities frequently lack lifesaving commodities to be able to provide maternal and newborn quality care services [ 16 ]. The 2013 and 2014 national service availability and readiness assessment (SARA) reports highlighted inadequacies in the availability of lifesaving drugs and equipment in most of the health facilities including higher-level referral health facilities [ 17 ].…”
Section: Introductionmentioning
confidence: 99%